Localization Matters: Epigenetic Regulation of Natural Killer Cells in Different Tissue Microenvironments - Wiedemann, Gabriela M. (Frontiers in Immunology, 2022)
Natural Killer cells (NK cells) are cytotoxic innate lymphoid cells (ILCs), which play a key role in the early protection against viral infection and cancer. In addition to mounting rapid effector responses, NK cells possess the capacity to generate long-lived memory cells to certain stimuli, thus blurring the lines between innate and adaptive immunity and making NK cells an ideal candidate for tumor immunotherapy. NK cell development, activation and memory formation, but also their functional properties are regulated by epigenetic alterations driven by a complex interplay of external and internal signals. These epigenetic modifications can convey long-lasting functional and phenotypic changes and critically modify their response to stimulation. Here, we review how NK cell functionality and plasticity are regulated at the epigenetic level in different tissue microenvironments and within tumor microenvironments. An in-depth understanding of the epigenetic modifications underlying NK cell functional diversity in different environments is an essential step in the development of NK cell-based cancer therapies.